Household Hedonic Price Model for Rice and its Attributes in Southwest Nigeria - Adewale, G. A.; Olubanjo, O.O.; Idowu, A.O.; Otunaya , A.O. (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2024)
It has been observed in Nigeria that the demand for locally processed Nigerian rice grains is low when compared to that of the imported rice grains. Hence, this study elicited empirical data on the attributes of rice grains that need to be put in place for locally processed Nigerian rice grains to become competitive with the imported ones and thereby increasing its demand in the local markets. Questionnaires were administered to 356 households in the Southwest, Nigeria. Hedonic price model was used to identify these rice attributes. Hedonic price model results show that ​rice grain price was positively affected by the white color of the grains (0.018) at the 10 per cent significance level. At the 1 per cent level, the coefficient for robust rice grain shape was (0.127) positive and significant. This suggests that households will gladly purchase rice grains at any price as long as they are white colored, robust shape, clean, sweet taste, and pleasant aroma. This study concludes that rice grains researchers and processors need to incorporate attributes of rice grains such as white color, robust shape, Cleanliness (absence of stones and chaffs), sweet taste, and pleasant aroma into the local variety so as to make it more acceptable and highly competitive with the imported ones in the local markets.